Older Adults’ Coping with the Digital Everyday Life - Rønning, Wenche M.; Sølvberg, Astrid M. (Seminar.net, 2017)
This study was motivated by a concern for how older adults adjust to their digital everyday life. Theories of motivation and self-efficacy are applied in order to understand how older adults master and adjust to the rapid development into a paper-free, online world. A sample of eighteen older adults (62-90 years) were interviewed about the reasons and motivations underlying their ICT usage, and how this affects their perception of mastering their everyday life. A semi-structured interview guide was developed for this purpose. The data were analyzed using an inductive coding procedure involving descriptive and interpretive phases based on the theoretical assumptions about motivation and mastery. Three overarching categories were evident in the data material; Challenges, Connectedness and Expanding. The first category describes new challenges mastering everyday life activities, and how this brings about feelings of pressure, barriers, and fear. The other two categories give a more positive picture of how older adults perceive the new developments. Internet and social media is perceived as positive because it enables them to stay connected to family, old and new friends. It also enables them to cultivate and expand leisure and hobby activities in new ways. Based on the findings we underscore the necessity of devising strategies that will prevent older people from being marginalized in relation to the digital everyday life.